Reduction of copper to steel weld ductility for parts in metallurgical equipment / Mohammad E. Matarneh and Nabeel S. Gharaibeh - E. Matarneh, Mohammad; S. Gharaibeh, Nabeel; Valeriy, V. Chigarev; Anatoliiovych, Havrysh Pavlo (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Despite being challenging, the welding of the dissimilar metals copper and steel is an essential process that is required for improving quality of equipment manufacturing in the fields of metallurgy, machine construction, and chemical industry. Restricted solubility of iron in copper leads to the formation of a supersaturated solid solution of iron and other chemical elements in the weld pool. Investigations have found the possibility of enhancing the process of welding copper with steel. In the case of using a flux-cored welding wire and an improved welding technique, the number of dendritic inclusions is reduced, and the weld ductility is improved. Studying the microstructure of a copper to steel weld confirmed the ability to enhance the outcome of the welding process of the dissimilar metals. The implementation of recommended preparation techniques of parts before welding, and optimization of the welding technique will increase the strength of the welds and, increases the operational reliability of metallurgical equipment.